MEMBONGKAR POLA PEMIKIRAN HUKUM FATWA DEWAN SYARI’AH NASIONAL (DSN) TENTANG PRODUK KEUANGAN SYARI’AH DAN PENYERAPANNYA DALAM HUKUM NASIONAL - Mugiyati . (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2014)
DSN-MUI is the only board that has the authority to issue a fatwa on the types of activities, products and financial services as well as overseeing the implementation of Shariah fatwa meant by Shariah financial institutions in Indonesia. As a religious fatwa should be the product of its legal reasoning bertemali kemasyarakatan.Oleh closely with social problems because it must be based DSN fatwa result of interaction between legal thinkers with the environment, in which the relevance of religious belief for the material world is often overlooked. In fact the National Fatwa Council of Sharia Shariah financial products follow three patterns of legal thought as a reference of the pattern of baya>ni> (semantic study), patterns qiya>si> (ta'li>li> or determination 'illat or legal factors), and the pattern istislahi> (considering the benefit based nash general) that three is a normative textual approach. Positifisasi efforts in response to the needs of the Muslims will be the implementation of Islamic law in the Indonesian economy missed by the Supreme Court of the Republic of Indonesia Regulation Number 02 of 2008 on Economic Shariah Law Compilation (KHES), which partially absorb the contents of fatwas National Sharia Board good in almost the same formula or refer in part.